2015
DOI: 10.1186/s12977-015-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-induced activation of HIV-1 in latently infected cell lines

Abstract: BackgroundDespite much work, safe and effective approaches to attack and deplete the long-lived reservoir of cells latently infected with HIV-1 remain an elusive goal. Patients infected with HIV-1 treated with cytotoxic agents or bone marrow transplantation can experience decreases in the reservoir of HIV-1 latently infected cells. Other viruses capable of long-term latency, such as herpesviruses, can sense host cell apoptosis and respond by initiating replication. These observations suggest that other viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 77 publications
(68 reference statements)
0
42
0
Order By: Relevance
“…By the same token, both NO donors and endogenously generated NO may stimulate HIV reactivation (113). Relatedly, Kahn et al (114) showed that anticancer conditioning agents (doxorubicin, etoposide, fludarabine phosphate, or vincristine) were able to induce HIV escape from latency and that this was associated with increased apoptosis rates (114). It is interesting to note that these drugs have been reported to induce oxidative stress (115)(116)(117), corroborating previous findings suggesting that the viral reservoir may be redox responsive and could potentially be eliminated by pro-oxidant drugs (118).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
“…By the same token, both NO donors and endogenously generated NO may stimulate HIV reactivation (113). Relatedly, Kahn et al (114) showed that anticancer conditioning agents (doxorubicin, etoposide, fludarabine phosphate, or vincristine) were able to induce HIV escape from latency and that this was associated with increased apoptosis rates (114). It is interesting to note that these drugs have been reported to induce oxidative stress (115)(116)(117), corroborating previous findings suggesting that the viral reservoir may be redox responsive and could potentially be eliminated by pro-oxidant drugs (118).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
“…These results indicate that proapoptotic proteins can increase HIV-1 replication and antiapoptotic molecules are able to inhibit HIV-1 replication, suggesting that HIV-1 has evolved ways to inhibit host cell apoptosis [12], an important way for the virus to enhance its replication when host cells initiate the apoptotic program as a way of limiting replication within the host. We and other investigators show that, in addition to HIV, infection with influenza virus (H1N1) [14], HSV-1 [12], KSHV [34], HHV6A, HHV6B, HHV7 and EBV [35] causes the host cell to undergo apoptosis and they adopt an emergency escape mechanism that leads to the rapid production of large amounts of virus. It has been shown that p53 expression is sufficient to initiate the emergency escape process [13].…”
Section: P53 Expression Affects Epigenetic Regulatorsmentioning
confidence: 91%
“…This phenomenon is called an Alternative Replication Program (ARP), a process when the host cell is undergoing apoptosis during viral infection. Viruses adopt an emergency escape mechanism to produce a large amount of virus rapidly [12]. Expression/activation of some pre-apoptotic molecules from apoptotic pathways, such as p53, Bax, Fas ligand, FADD, caspase-3, and caspase-8 are sufficient to initiate the ARP in HIV-1 infection [13] and influenza A virus infection [14].…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication from Zeichner laboratory indicated that cancer chemotherapeutic agents that induce apoptosis dramatically activated HIV-1 replication in latently infected cells. 33 The authors based their study on the observation that cytotoxic chemotherapy and bone marrow transplantation applied to HIV patients who developed lymphoma and appeared to be relatively more effective at depletion of the HIV-1 latent reservoir than LRAs. 34,35 In fact, treatment of both persistently HIV-1-infected T cells and monocytes with cytotoxic drugs, doxorubicin, etoposide, fludarabine phosphate, or vincristine, was associated with caspase-3 and -8 activation and therefore apoptosis response that followed dramatic increase of HIV-1 RNA and p24 count.…”
mentioning
confidence: 99%